تأثير المستخلص المائي لأزهار الكركديه على مستويات الكولسترول الكلي والشحوم الثلاثية وسكر الدم في الأرانب المعرضة للتسمين - دباغ, مروان; علي, اكتمال; الراعي, أحمد (Latakia University Journal -Biological Sciences Series, 2016)
ﺃﺠﺭﻴﺕ هذه ﺍﻟﺩﺭﺍﺴﺔ في مخابر كلية العلوم في ربيع العام 2013حيث ﻗﺴﻤﺕ ﺤﻴﻭﺍﻨﺎﺕ ﺍﻟﺘﺠﺭﺒﺔ ﻋﺸﻭﺍﺌﻴا إلى بعد أن أخضعت للتسمين لمدة 4 أسابيع عن طريق عليقة قياسية مضاف اليها دهن حيواني بنسبة 3% إﻟﻰ مجموعتين بواقع 6 أرانب لكل مجموعة حيث جرعت أرانب المجموعة التجريبية بمستخلص الكركديه بتركيز 150ملغ/كغ من ﻭﺯﻥ ﺍﻟﺤﻴﻭﺍﻥ ﻋﻥ ﻁﺭﻴﻕ ﺍﻟﻔﻡ ﻟﻤﺩﺓ أﺭﺒﻌﺔ ﺍﺴﺎﺒﻴﻊ بينما أخذت حيوانات المجموعة الشاهدة الغذاء والماء بشكل حر.جمعت عينات ﺍﻟﺩﻡ مع نهاية كل أسبوع من أسابيع التجربة الأربعة ﻤﻥ ﺠﻤﻴﻊ ﺍﻟﺤﻴﻭﺍﻨﺎﺕ، وﺘﻡ خلالها ﻗﻴﺎﺱ ﻤﺴﺘﻭﻴﺎﺕ الكوليسترول الكلي والشحوم الثلاثية وغلوكوز الدم في مخبر الكيمياء الحيوية التابع للمعهد التقاني الطبي في جامعة تشرينأظهرت نتائج التحليل الإحصائي أن المعاملة بالمستخلص المائي أدت إلى انخفاض معنوي(P<0.05) في مستويات كل من الكولسترول الكلي والشحوم الثلاثية وغلوكوز الدم بعد أربعة أسابيع من التجريع بالمستخلص مقارنة بالشاهد، كما سجلت فروق معنوية بين أسابيع التجربة المختلفة في مجموعة الحيوانات التجريبية حيث أظهرت الدراسة وجود علاقة عكسية بين مستويات شحوم الدم والغلوكوز من جهة وتركيز المستخلص المائي مع زيادة فترة التجريع بمرور الزمن. This study was conducted in the laboratories of the Faculty of Science In the spring on 2013, after being subjected to gavage for 4 weeks through a standard diet supplemented fat by 3% to two groups (6animales per group) the experimental group became aqueous extract 150 mg/kg Body weight for 4weeks while the control group became standard food and tap water ad libitum. The Blood samples were collected each week, and then the serum samples were taken to the biochemical tests to determine total cholesterol, triglycerides and glucose levels in biochemistry laboratory of the Institute of Intermediate medical in Tishreen University. The results showed significant decrease (P<0.05) in total cholesterol, triglycerides and glucose levels , after administration of H. sabdariffa aqueous Extract in experiment group in contrast to control group , we reported significant differences in cholesterol, triglycerides and glucose levels between weeks of administration in the experimental group, where the study showed an inverse relationship between blood lipids and glucose levels on the one hand and the concentration of aqueous extract with an increased dosage over a period of time .